The Aesthetic of Aniconism: Analyzing the Socio-Cultural Negotiation of Islamic Principles in the Decorative Motifs of Pandai Sikek Songket - Purwo Prihatin; Sunarmi Sunarmi; Andar Indra Sastra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Pandai Sikek Songket is a cultural heritage of the Minangkabau people, rich in aesthetic and philosophical values. Its decorative motifs were initially influenced by natural elements and local customs that developed since the pre-Islamic era. However, with the arrival of Islam in Minangkabau, these motifs underwent a transformation toward alignment with Islamic values. The influence of Islam is reflected in geometric patterns, the reduction of figurative motifs, and philosophies that embody Islamic ethics and teachings. The purpose of this study is to explain the transformation of Pandai Sikek Songket motifs within the context of the encounter between Minangkabau customs and Islamic values, and to explore how this process of cultural adaptation occurs harmoniously without diminishing the essence of local identity. This study employs a qualitative method with a descriptive-analytical approach. Data were collected through literature review, interviews, and observational documentation, followed by an analysis of Pandai Sikek Songket motifs that have undergone stylization. To examine the influence of Islam, the research applies the theories of acculturation and Islamic aesthetics to understand how Islam shaped the motifs of Pandai Sikek Songket as a traditional textile. The findings conclude that the influence of Islam on Pandai Sikek Songket motifs occurred through a process of harmonious cultural adaptation. Elements of custom and nature were preserved but reinterpreted in accordance with Islamic values, such as the use of symmetrical patterns, stylized forms, and symbolic meanings that reflect Islamic principles. The harmonization of tradition, nature, and Islam in Pandai Sikek Songket illustrates the cultural flexibility of the Minangkabau people in embracing change without losing their identity. The contribution of this study lies in strengthening the understanding of how traditional cultural heritage can transform through the dialogue between custom, nature, and religion, thereby enriching the discourse on Islamic aesthetics and Nusantara culture. The findings also reveal that the harmony between tradition, nature, and Islam in Pandai Sikek Songket reflects the cultural flexibility of the Minangkabau community in adapting to change while preserving its authentic identity.